Designing RIMCOTS Model for Risk Identification and Mitigation for COTS- based Software Development - Kaur, Amandeep (My University, 2011)
COTS-based software development (CBSD) shifts the emphasis from programming software to composing software systems from off-the-shelf components. Component based software development is often considered as a low risk development strategy, which provides a simple and rapid mechanism for developing software systems from pre-existing and proven components. In reality COTS-based software development carries significant risks throughout the software development life cycle. These risks can be due to the nature of COTS components, development process, component technologies and vendor support. The part of thesis work involves an approach to design a RIMCOTS model that incorporates risk identification and risk management mechanism for mitigation of risks in the COTS-based software development. The purpose of this thesis work is to identify, analyze and explore critical risks in various stages of COTS-based software development that can affect long-term viability of software systems. The Proposed RIMCOTS model includes techniques for evaluating and mitigating risks associated with deploying COTS components in Component based software systems and serves as a guide for how to manage multiple COTS software components in complex COTS-based systems. We validate this proposed RIMCOTS model by using CURE methodology.
Keywords: Designing RIMCOTS Model; Software Development